Faktor Penarik dan Faktor Pendorong Mobilitas Eks Tki Desa Purworejo Kecamatan Ringinarum Kabupaten Kendal - Rochaniyah, Nina; Indrayati, Ariyani (Edu Geography, 2019)
This study aims to determine 1) the environmental conditions of the coastal area, 2) the perception of pond farmers in the preservation of the coastal area environment in Ketawangrejo Village, 3) the participation of pond farmers in environmental conservation in the coastal area in Ketawangrejo Village, Grabag District, Purworejo Regency. The population in this study were 120 pond farmers. The sample of this study was 30 pond farmers with Proportionate Stratified Random Sampling techniques. Data collection techniques used observation, questionnaires, documentation and interviews. The data analysis technique uses descriptive percentages. Based on the results of the study, it can be seen that the condition of coastal areas has environmental degradation due to the conversion of agricultural land and forests into aquaculture areas and has a dense impact on agricultural area pollution. Farmers have understood and taken the initiative in responding to problems in the coastal area through actions to improve and preserve the coastal area. Participation of pond farmers in organizations tends to be passive from 4 forms of participation, namely partitioning ideas or ideas, energy, funds, and facilities. Banyaknya pencari kerja yang tidak diimbangi dengan ketersediaan lapangan kerja membuat banyak penduduk Desa Purworejo melakukan moblitas antara negara menjadi Tenaga Kerja Indonesia (TKI). Setiap mobilitas yang dilakukan memiliki faktor penarik dan faktor pendorongnya masing-masing. Penelitian ini bertujuan untuk mengetahui besarnya mobilitas, faktor penarik dan pendorong mobilitas yang dilakukan oleh eks TKI Desa Purworejo dari tahun 1985-2015 serta persebaran berdasarkan negara tujuan. Pengambilan sampel menggunaan metode proporsional random sampling, dengan sampel sebanyak 90 orang. Penelitian ini menggunaan metode kuantitatif. Data dikumpulkan dengan kuesioner, wawancara dan dokumentasi, dianalisis dengan menggunakan metode deskriptif . Hasil penelitian menunjukkan mobilitas tertinggi yang dilakukan oleh eks TKI adalah negara tujuan Hong Kong sebanyak 29%, Taiwan 26%, Arab Saudi 16%, Malaysia dan Singapuran 10% serta Korea Selatan dan Uni Emirat Arab sebesar 4%. Faktor-faktor penarik diantaranya adalah gaji, remitan, jaminan ibadah, bahasa pengantar dan ajakan dari saudara/teman.